The mother and the young child: Who programs whom - Sorin Buzinschi (Amaltea Medical Publishing House, 2020)
Intrauterine life is regulated by an epigenetic programme which adapts fetal life to the current and presumed conditions. The fetal programming determined by maternal nutritional disorders is at the origin of some metabolic and cardiovascular diseases of childhood and adult life. The maternal programming guides the child's immunity, circadian rhythm, and stress response. The maternal and paternal imprinted genes exert a contradictory action upon fetal development (the war of the sexes). In turn, the fetus programs the maternal physiology through placental hormones and the cell transfer in the maternal organism (feto-maternal microchimerism).